Semester System and Its Implementation at Prithvi Narayan Campus: What Do Postgraduate Students Say - Baral, Uma Nath; Chhetri, Than Bahsdur; Subedi, Girdhari (Prithvi Journal of Research and Innovation, 2019)
In pursuit of the quality education, from the academic session 2018, Tribhuvan University (TU) launched the semester system, replacing the annual system in the postgraduate level to all its constituent and affiliated campuses across the country. As a constituent campus of TU, Prithvi Narayan Campus has started the new academic year under the semester system in all master’s degree programs. Implementing the semester system itself is not sufficient to attain quality education. It needs some basic requirements for its successful operation in place of the old annual system that was presumed to fail in delivering quality education. Full-time students, professional teachers, applied and innovative curriculums, scientific teaching methods, a resourceful library, a learning environment and a prompt academic calendar are essential requirements for a well-functioning semester system. To find out the perceptions and evaluations of the postgraduate students on some of the basic requirements of the semester system is the basic objective of this research paper. Class census surveys and informal interviews were conducted in seeking the required data to fulfill the objective of this paper.